Attractive Tourist Destinations as a Factor of its Development - MOROZOV, Mikhail А.; MOROZOVА, Natalia S. (Journal of Environmental Management and Tourism; Vol 7 No 1 (2016): JEMT Volume VII, Issue 1(13) Spring 2016, 2016)
The article deals with the formation of attractive tourist destinations. It is shown that the attractiveness acts as a major motivational factor in the choice of tourist destinations (destinations) and forms a tourist need. Tourist attraction destination can be formed spontaneously or purposefully. The basic tools formation of the tourist areas are tourist destinations and tourism clusters. The main factors what influencing the formation of the tourist attractiveness of the destination are discussing. The classification of tourist attraction on various grounds: on the area of occurrence of appeal, the duration of its existence, the degree of controllability appeal. It is proposed to allocate and evaluate the three levels of appeal: There is, realistically achievable and the potential attractiveness of a tourist destination. A model assessment of attractive tourist destinations is approaches.
Keywords: tourist destination; an attractive tourist destination; the cluster model for evaluating the attractiveness of tourist destinations